Impelementasi Monitoring Digital Siswa (MODIS) untuk Mewujudkan Profil Pelajar Pancasila di Sekolah - Triono Ali Mustofa; Dewi Nur Priastuti (Journal of Education and Religious Studies, 2022)
The purpose of this research article is to explain how Student Digital Monitoring (MODIS) is implemented in schools and identify the components that support and inhibit it. This research is based on qualitative research with phenome-nological design conducted at SMP Muhammadiyah 8 Surakarta. The data collection methods used are interviews, observation, and documentation. The findings of this research article are that the implementation of MODIS as a program aims to improve the character and ability of students in accordance with Profil pelajar Pancasila, namely faith, piety, and noble character. Monitoring activities are carried out on student worship activities at home through digital supervision of students, there are three indicators that are in accordance with the profile of Pancasila students: faith and piety, which is shown by prayer and recitation, and noble character, which is shown by birrul walidain, or filial piety to both parents. Supporting and inhibiting factors for digital monitoring of students include the presence of devices, internet networks, or internet, and parental support. This student digital monitoring program can run well and achieve school goals with this supporting element. One of the obstacles is poor skills in filling out Google forms due to the absence of a data plan and steps that are too complicated. To solve this problem, schools have created barcodes and given penalties to students who don't.